PERKEMBANGAN MUSIK HIP-HOP SEBAGAI PRODUK BUDAYA POPULAR AMERICAN MUSIC AND RADIO MUSIC, RACE, AND CULTURE (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2014)
This research describes about the growth of popular culture with one relevant example of popular culture product called music but with the specific mainstream called Hip-Hop. This era is also well known with the era of technology and the spread worldwide quickly rather than we thought. Advances in technology now moves so quickly that directly affect the lives of people in the world, for example with new innovations with all the advantages that make it as a product that is consumed and even become a role model gadget by the society such as iPod, Music, Internet, Hollywood Movies, Jeans, BlackBerry, iPhone, Music, Barbie, etc. America is a highest standard for these products then the power of mass media distribute through advertisements, songs, movies, internet, cable tv and deploy these products to the world and then consumed by society who later became part of our daily lives . These products are known as popular culture. One way to find out is the study of popular culture is through music. The music certainly can not be separated from popular culture because it is a culture that has a lot of fans around the world virtually. In this paper the author tried to theme music Hip-Hop as the study of popular cultureproducts.